2021
DOI: 10.1007/s13202-021-01340-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of pore network and influencing factors of methane adsorption capacity of transitional shale from the southern North China Basin

Abstract: Quantitative characterization of pore structure and analysis of influencing factors of methane adsorption are important segments in shale gas reservoir and resources evaluation and have not been systematically carried out in marine–continental shale series. A series of integrated methods, including total organic carbon (TOC) contents, Rock-Eval pyrolysis, mineral composition analysis, pore structure measurement, high-pressure CH4 adsorption analysis and FE-SEM observation, were conducted on 12 transitional sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The micropores of shale matrices mainly accommodate adsorbed CH 4 . The adsorption mechanism of CH 4 on shale matrices typically consists of surface coverage and micropore filling. , Hence, the correlation analysis between the micropore structure parameters and CH 4 adsorpiton capabilites of shale matrices was conducted to reveal the possible adsorption mechanism. The pore classification method raised by the International Union of Pure and Applied Chemistry (IUPAC) was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…The micropores of shale matrices mainly accommodate adsorbed CH 4 . The adsorption mechanism of CH 4 on shale matrices typically consists of surface coverage and micropore filling. , Hence, the correlation analysis between the micropore structure parameters and CH 4 adsorpiton capabilites of shale matrices was conducted to reveal the possible adsorption mechanism. The pore classification method raised by the International Union of Pure and Applied Chemistry (IUPAC) was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that micropores developed in clay provided a considerable specific surface area, which was conducive to the adsorption capacity of shale. Liu et al also reported a similar conclusion and stated that clay content was the primary influencing factor of shale adsorption capacity. However, more studies suggested that shale adsorption capacity was dominated by organic matter content. Jiang et al and Xie et al normalized the CH 4 adsorption amount by TOC to avoid the influence of organic matter pores and found a linear positive correlation of clay content versus normalized value.…”
Section: Influence Of Clay Content On Ch4 Adsorption Capacity In a Sh...mentioning
confidence: 56%
“…Liu et al 34 demonstrated that micropores developed in clay provided a considerable specific surface area, which was conducive to the adsorption capacity of shale. Liu et al 35 also reported a similar conclusion and stated that clay content was the primary influencing factor of shale adsorption capacity. However, more studies suggested that shale adsorption capacity was dominated by organic matter content.…”
Section: Influence Of Clay Content On Chmentioning
confidence: 57%
See 2 more Smart Citations